Transport of Carbonate Ions by Novel Cellulose Fiber Supported Solid Membrane - A. G. Gaikwad (Bulletin of Chemical Reaction Engineering & Catalysis, 2012)
Transport of carbonate ions was explored through fiber supported solid membrane. A novel fiber supported solid membrane was prepared by chemical modification of cellulose fiber with citric acid, 2′2-bipyridine and magnesium carbonate. The factors affecting the permeability of carbonate ions such as immobilization of citric acid-magnesium metal ion -2′2-bipyridine complex (0 to 2.5 mmol/g range) over cellulose fiber, carbon-ate ion concentration in source phase and NaOH concentration in receiving phase were investigated. Ki-netic of carbonate, sulfate, and nitrate ions was investigated through fiber supported solid membrane. Transport of carbonate ions with/without bubbling of CO2 (0 to 10 ml/min) in source phase was explored from source to receiving phase. The novel idea is to explore the adsorptive transport of CO2 from source to receiving phase through cellulose fiber containing magnesium metal ion organic framework. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)